Synthesis and Study of a Persistent Selenenic Acid and Preliminary Studies of Thiol Oxidation - Presseau, Nathalie (Université d'Ottawa / University of Ottawa, 2014)
Selenenic acids and other organoselenium compounds are important both in organic and biochemistry. In organic chemistry, syn-elemination of selenoxides is used to prepare alkenes, giving a selenenic acid by-product. In biochemistry, selenocysteine is catalytically active in a variety of selenoenzymes, which have antioxidant properties, and is oxidized to a selenenic acid intermediate. For example, glutathione peroxidase (GPx) plays a role in fighting oxidative damage by catalyzing the reduction of hydroperoxides. Previous studies have shown that the lighter chalcogen analogue of selenenic acid, sulfenic acid, is a powerful antioxidant and that the known antioxidant activity of garlic is attributable to the 2-propenesulfenic acid derived from the compound allicin. This has prompted questions concerning the role of selenenic acid in the antioxidant activity of organoselenium compounds. In order to study the physiochemical properties of selenenic acids –a functional group about which little is known—and to evaluate their potential as antioxidants, a persistent selenenic acid is needed. Herein, the model compound, 9-triptyceneselenenic acid, is prepared by a previously reported procedure and a new pathway is designed, such that its properties and reactivity can be studied. The oxidation of thiols is important in cell signalling, leading to the disulfide bonds implicated in post-translational modification, among other biological roles. While this reaction is presumed to occur through the reaction of thiol with an oxidant that forms sulfenic acid, and from a subsequent reaction of sulfenic acid with another thiol, sulfenic acids are so reactive that they are not usually seen as intermediates. Given the stability of the 9-triptycenesulfenic acid previously synthesized, preliminary kinetic study of the oxidation of 9-triptycenethiol to its corresponding sulfenic acid is made possible.
Keywords: selenenic acid; sulfenic acid; organoselenium; antioxidant